S21: Empowering Healthcare Providers as Physical Activity Champions: Experiences From Around the World (Baltic Journal of Sport and Health Sciences, 2026)
Physical inactivity is a complex public health issue that requires multi-level, multi-sectoral approaches. Systems-based approaches address this complexity by addressing upstream determinants of health and intersectoral collaboration and partnerships. Addressing physical inactivity through healthcare settings is one of the International Society of Physical Activity and Health’s (ISPAH) ‘eight investments that work for physical activity’. Healthcare professionals come into frequent, recurring contact with large proportions of the population, especially those with physical inactivity-related health conditions. Further, healthcare professionals are widely respected and trusted, which translates into having considerable potential to support patients in changing their physical activity behaviour. WHO’s Global Action Plan on Physical Activity (GAPPA) describes the need to create active systems, which includes strengthening the physical activity training of current and future health professionals (e.g. doctors, nurses, allied health professionals) to ensure that they can conduct an assessment, provide brief advice, and/or counselling on physical activity in clinical practice. However, few health professional training programmes systematically provide education or training on the basics of physical activity counselling as a part of the patient care process. In a survey of HEPA Europe members in the Physical Activity Promotion in Healthcare Settings working group, ‘training of healthcare professionals’ was the top priority listed among the major challenges that needed to be addressed by the group. Thus, this symposium will feature several examples from across the globe of how physical activity training programmes were specifically developed, integrated, and evaluated for future and current healthcare professionals, with the ultimate goal of sharing best practices with the audience that they can appeal to with their local health systems, health professionals, and academic training programmes.